Sleep structure and electroencephalographic spectral power of middle‐aged or older adults: Normative values by age and sex in the Korean population. (5th May 2021) - Yoon, Jee‐Eun; Oh, Dana; Hwang, Inha; Park, Jung Ah; Im, Hee‐Jin; Lee, Seung Ku; Jung, Ki‐Young; Park, Seong‐Ho; Thomas, Robert J.; Shin, Chol; Yun, Chang‐Ho
Abstract: The fine structure of sleep electrocortical activity reflects health and disease. The current study provides normative data for sleep structure and electroencephalography (EEG) spectral power measures derived from overnight polysomnography (PSG) and examines the effect of age and sex among Korean middle‐aged and older adults with or without obstructive sleep apnea (OSA). We analysed home PSG data from 1, 153 adult participants of an ongoing population‐based cohort study, the Korean Genome and Epidemiology Study. Sleep stages were visually scored and spectral power was measured on a single‐channel EEG (C4‐A1). We computed spectral power for five frequency ranges. The EEG power was reported in relative (%) and log‐transformed absolute values (µV 2 ). With ageing, the proportion of N1 sleep increased, whereas N3 decreased, which is more noticeable in men than in women. The amount of N3 was relatively low in this cohort. With ageing, relative delta power decreased and alpha and sigma power increased for the whole sleep period, which was more pronounced during REM sleep in non‐OSA. For men compared with women, relative theta power was lower during REM and sigma and beta were higher during N1 sleep. The differences of relative powers by age and sex in OSA were comparable to those in non‐OSA. In a community‐based Korean population, we present normative data of sleep structure and spectral power for middle‐aged or older adults of a non‐Caucasian ethnicity. The values varied with age and sex and were not influenced by sleep apnea.